Concept of Research on Entrepreneurship and Innovativeness of Enterprises in Peripheral Regions of North-Eastern Poland - Zbigniew NASALSKI (Communications of International Proceedings, 2022)
The aim of the study was to define the concept of research on entrepreneurship and innovation of enterprises in the peripheral regions of north-eastern Poland. With regard to peripheral regions, it is necessary to systematically diagnose the state of entrepreneurship and innovation of enterprises and to improve the most important elements of the economic system from the point of view of competitiveness, including: strategies for the development of economic entities, the mechanism of the impact of the business environment on economic entities and pro-entrepreneurial activity of local governments. The presented research concept can effectively support the diagnostic and developmental aspects of the regions.
Keywords: entrepreneurship; innovation; peripheral regions; regional development